Effect of leech therapy on body composition parameters / Nazihah Ahmad - Nazihah, Ahmad (2012)
Leech therapy treatment is one of the complimentary and alternative medicine that has been categorized as one of the ancient method in treating diseases. Locally unpopular this treatment still has its own believer that practices it for the sake of bloodletting treatment that claims to be successful. Therefore, a series of study should be conducted in order to prove the aforementioned claim by using the bioimpedance analysis. Bioimpedance analysis is way of measuring the fat and fat free mass in much more convenience way. This measurement is normally used by nutritionist as this invasive method is very suitable to determine the health of a person which directly affected by the composition of the fat in the body that can be further subdivide into water, mineral and protein constituents. The result could be used to measure the effectiveness of the leech therapy treatment as the readings and changes are taken into consideration before and after the treatment. Thus, using engineering tools to analyze the result can prove the effect of this therapy quantitatively.